The Role of Universities in Preparing Local Governments for the Era of 5.0 Society - Abdul Nadjib (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aimed to identify the challenges of the 5.0 Society era and the role of universities in preparing local governments to face such challenges. This research was carried out by following the stages of a systematic literature review which consisted of designing a review, carrying out a review, analyzing, and writing a review report. The data were taken from national and international electronic scientific journals related to the topic being studied. Data were collected by purposive sampling using certain keywords through the google search engine. The collected data was then analyzed using content analysis techniques. This research found that various challenges must be faced in 5.0 Society, and universities have a strategic role in preparing the government to develop strategies to turn the challenges of 5.0 Society into opportunities both in terms of preparing the necessary human and technological resources. The findings of this research, First, the challenges of local governments in entering the era of Society 5.0 include the readiness of human resources and technology. Second, in facing these challenges, universities have a vital role in helping local governments. Universities, as centres of technology development and dissemination, are able to assist local governments in preparing and improving the quality of human resources and technology required by local governments. For this reason, it is recommended that local governments collaborate with various universities so that they are ready to enter the Society 5.0 era and are able to turn these challenges into opportunities.